2010
DOI: 10.1248/bpb.33.1223
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effect of Drosophila Deoxynucleoside Kinase Gene on Replicating Plasmid in HeLa Cells

Abstract: Gene delivery with nonviral vectors is a promising approach, due to its excellent safety profile in comparison to that of viral vectors. [1][2][3][4][5] However, low and transient transgene expression is a major concern for nonviral vectors. One of the keys to overcome this problem would be the establishment of an efficient and targeted delivery system, in which intracellular trafficking is considered. In addition, the controlled intranuclear disposition of the delivered plasmid would be quite important for ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…These data reveal that the residues Tyr70 and Arg105 take into consideration the positioning of dFdC, suggesting its significant implications for therapeutic efforts due to the broad substrate acceptance of Dm-dNK. Characterized by its high catalytic property and broad substrate acceptance, Dm-dNK has therapeutic potential and is used in the treatment of several cancer types (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…These data reveal that the residues Tyr70 and Arg105 take into consideration the positioning of dFdC, suggesting its significant implications for therapeutic efforts due to the broad substrate acceptance of Dm-dNK. Characterized by its high catalytic property and broad substrate acceptance, Dm-dNK has therapeutic potential and is used in the treatment of several cancer types (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these data underline the importance of its potential role as a suicide gene. Therefore, Dm-dNK has been used successfully in suicide gene therapy against a wide variety of cancers (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the catalytic rate of the enzyme for pyrimidines is 100-600 times higher than for purines (Munch-Petersen et al, 1998a;Munch-Petersen et al, 2000). All these data underline the importance of the potential role of Dm-dNK as a suicide gene, and therefore, this gene have been used (Ito et al, 2010;Ma et al, 2011;Zhu et al, 2011b;Ma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%